Revisiting Grammatical Complexity in L2 Writing via Exploratory Factor Analysis - Lan, Ge; Li, Xiaorui; Zhang, Qiusi (Frontiers in Psychology, 2022)
Since the 1990s, grammatical complexity has received substantial research attention in applied linguistics (Bulté & Housen, 2014). The representation of grammatical complexity has expanded over the 1990s to the 2010s in L2 writing, in response to Norris and Ortega’s (2009) claim that this construct should be studied as a multi-dimensional construct. This expanding representation of grammatical complexity is also summarized in recent publications (e.g., Lan, Liu & Staples, 2019). While acknowledging the importance of these research syntheses, we find it equally important to revisit grammatical complexity from an inductive perspective. An exploratory factor analysis (EFA) was applied to explore latent dimensions (i.e., factors) of grammatical complexity in L2 writing. We analyzed Lu’s (2011) 14 grammatical complexity measures in the L2 corpus of the British Academic Written English Corpus. In terms of the results, we proposed a four-factor model with “clausal subordination”, “phrasal construction”', “global length unit” and “others”. The four factors generally align with the types of grammatical complexity proposed in Lu (2011), but differences on six measures are also found. Noteworthy points were discussed to interpret the reasons behind the differences. Research implications are provided to show further research directions.